Improving Teacher's Professionalism to Increase The Quality of Hindu Religious Education in School - Ni Nyoman Perni; Hary Yati Paramitha (UHN IGB Sugriwa Denpasar, 2020)
This study aims to analyze the improvement of teacher professionalism to improve the quality of Hindu religious education through the effectiveness and creativity of interaction patterns in schools. School as a formal education is an institution that should shape students to be individuals with noble character. This educational institution should be able to equip its students with a variety of values, attitudes, and abilities and a strong enough basic skills as a basis for living a real-life in society. A high character person of Hindu religious education are carried out continuously at all levels of education. Hindu religious education can realize the goals of national education which is to develop the potential of students. Later on, there are expected to become human beings who believe in and fear God Almighty, have noble, healthy, knowledgeable, capable, creative, independent, and be democratic and responsible citizens. Furthermore, the improvement of the quality of Hindu religious education must be implemented by increasing the effectiveness of learning interaction patterns at schools.